2014
DOI: 10.1155/2014/479286
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Framework for Website Usability

Abstract: With the major advances of the Internet throughout the past couple of years, websites have come to play a central role in the modern marketing business program. However, simply owning a website is not enough for a business to prosper on the Web. Indeed, it is the level of usability of a website that determines if a user stays or abandons it for another competing one. It is therefore crucial to understand the importance of usability on the web, and consequently the need for its evaluation. Nonetheless, there ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 51 publications
(72 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, as Law and van Schaik (2014) discuss, in UX empirical studies, variables such as fl ow, aestheticbeauty, emotion, enjoyment, affect, arousal/ valence, hedonic quality, intrinsic motivation, presence, engagement, attractiveness, and satisfaction are observed. Dingli and Cassar (2014) proposed Intelligent Usability Evaluation framework which goal is to minimize the amount of human intervention necessary to evaluate the usability of the website. By entering a homepage URL, the user issues a request to have a list of interior webpages to be evaluated for usability.…”
Section: Informační Managementmentioning
confidence: 99%
“…Furthermore, as Law and van Schaik (2014) discuss, in UX empirical studies, variables such as fl ow, aestheticbeauty, emotion, enjoyment, affect, arousal/ valence, hedonic quality, intrinsic motivation, presence, engagement, attractiveness, and satisfaction are observed. Dingli and Cassar (2014) proposed Intelligent Usability Evaluation framework which goal is to minimize the amount of human intervention necessary to evaluate the usability of the website. By entering a homepage URL, the user issues a request to have a list of interior webpages to be evaluated for usability.…”
Section: Informační Managementmentioning
confidence: 99%
“…Several researchers have contributed to the development of automated usability evaluation tools [17], [14], [18], [19]. Schiavone and Paterno [14] proposed Mauve -a tool for automated usability evaluation capable of evaluating WUI conformance to WCAG accessibility guidelines of all three levels from A through AAA, containing around 80 different guidelines.…”
Section: Related Workmentioning
confidence: 99%
“…Considering the growing importance of accessibility and usability evaluation of websites, several research have been conducted and are still going with focuses on different genre of websites [12][13][14][15]. The work of [7] which focussed on airline websites comparison in Turkey in 2012 and 2014 revealed that efforts were made by the owners of the selected airline websites to improve the functionalities (accessibility and usability issues) of their websites.…”
Section: Related Workmentioning
confidence: 99%